Lower limb kinematic, kinetic, and EMG data from young healthy humans during walking at controlled speeds - Luís Moreira (Nature Portfolio, 2021)
Measurement(s) walking • Lower Extremity Technology Type(s) motion capture • electromyography • force platform Factor Type(s) sex • age • height • mass • leg length • foot length Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13169348